Self-directed learning in video games, affordances and pedagogical implications for teaching and learning. (September 2020) - Toh, Weimin; Kirschner, David
Abstract: Self-directed learning is becoming increasingly important in the twenty-first century due to the rapid changes caused by technological advancement and automation, which necessitate a shift in the learning models adopted by students from a more teacher-directed to a more student-centred pedagogy. Video games can be leveraged to develop self-directed learning in students because digital play environments are engaging and possess features conducive for independent learning, such as safe spaces and authentic learning environments. Our aim in this paper is to first derive a set of self-directed learning strategies in video games that can be adopted for use in pedagogical contexts. Second, the coding scheme of self-directed learning strategies can be used to evaluate video games for their suitability for developing self-directed learning strategies in students. User experience approaches such as interviews and the think-aloud protocol were used to analyse the gameplay videos of the study's participants for deriving the coding scheme of the self-directed learning strategies. Based on player experience, we also derived a set of factors that promoted self-directed learning in video games. These factors can be integrated by educators and user experience designers to improve video game design to foster the development of self-directed learning strategies in students. Highlights: We derived a coding scheme of self-directed learning (SDL) strategies in video games. The coding scheme can be used to evaluate video games' potential to support SDL. User experience approaches were used to analyse the gameplay videos. We also derived the factors that promoted SDL in video games.